Recommendations for collection and development strategy of waqf funds: A case study on waqf institutions - Putri Purwandari Hasan; Elvia R. Shauki (Jurnal Ekonomi dan Keuangan Islam, 2022)
Purpose – This study aims to examine phenomena related to the collection and development of waqf funds by waqf institutions and formulate recommendations regarding applicable strategies to optimize the collection and development of waqf funds based on the principles of commitment-trust theory.